IN SILICO HOMOLOGY MODELING AND EVOLUTIONARY ANALYSIS OF GROWTH HORMONE PROTEIN FROM ANDRIAS DAVIDIANUS - HAI-FENG TIAN,; HAN-BING XIAO,; YAN MENG,; QIAO-MU HU, (International Journal of Pharma and Bio Sciences, 2015)
Chinese giant salamander (Andrias davidianus), a critically endangered amphibian species endemic to China, has been artificially bred successfully. Among artificial breeding populations, great growth differences were found. Growth hormone (GH) is a peptide hormone that stimulates postnatal growth in diverse vertebrates. The primary sequence of GH of A. davidianus (AdGH) was analyzed and its tertiary model of AdGH was generated through homology modeling, validation and molecular dynamic simulation. Phylogenetic analysis based on the GH from vertebrates was carried out, and lineages-specific gene duplication occurred frequently. The present study suggests AdGH might involves in regulating growth rate since its conservation in primary sequence and tertiary structure, however, additional studies are needed to fully illustrate its precise physiological roles because of lineage- and species-specific gene duplications are present in other species.